Relationship between Obesity and Food Habits among Female Adolescents - ES Hajikazemi; Moghaddam M; Hosseini AF; Heidarikhayat N (Iran University of Medical Sciences, 2012)
Background & Aims: Obesity which is produced due to excessive accumulation of fat in body compartments could result from imbalance between intake and consumption of energy and is related to the food habits of each person. The aim of this study was to assess obesity and its relationship with female adolescents' food habits in Tehran.   Material & Methods: It was a predictive correlational study. The sample consisted of 385, 14-18 year old female students in west of Tehran. The students were recruited by multistage random sampling. Data was collected by Food Frequency Questionnaire, caliper, tape measure and measurement scale and analyzed by ANOVA, Pierson correlation and multiple regression tests using SPSS-PC (v.14).   Results: According to the findings, %18 of the students were overweight and obese based on Triceps skin fold thickness and %15 were overweight and obese based on body mass index. Frequency of daily consumption of bread and cereals, rice, fat, soft drinks and egg among overweight and obese students were significantly higher than other groups (p<0.05).   Conclusion: Due to the high consumption of unhealthy food among overweight and obese girls the prevalence of chronic diseases associated with obesity in the future is disturbing. Therefore, promotion of healthy nutrition and health education in schools and families by those involved in the health sector particularly community health nurses seem to be necessary.  Received: 17 Jun 2012   Accepted: 22 Aug 2012